Impulse Buying Behavior of Generation Z People on Shopee - Made Kumara Dewi; IB Teddy Prianthara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The development of technology in the digital era has changed the pattern of people's shopping behavior, especially with the emergence of e-commerce that facilitates online transactions. Shopee as one of the largest e-commerce platforms in Indonesia, attracts consumer attention through marketing strategies such as e-WOM, high product quality, and flash sale promos Generation Z, the most active consumer group in the digital world, tends to make impulse purchases triggered by emotional urges and external stimuli. This impulse buying phenomenon is important because it can affect consumption patterns and the financial well-being of consumers, especially among Generation Z. This study aims to analyze the influence of e-WOM, product quality and flash sales on Generation Z's impulse buying behavior on the Shopee platform. Data was collected through a survey using a questionnaire distributed to respondents who met the criteria, namely Generation Z who actively shop at Shopee. The sampling technique used was purposive sampling, with a total of 190 respondents. Data analysis using Structural Equation Model (SEM) based on Partial Least Square (PLS) to test the relationship between variables. The results of the study are expected to provide deeper insights into impulse shopping behavior in Generation Z, as well as provide recommendations for e-commerce.